Correction: Impact of combined exercise training on the development of cardiometabolic and neuroimmune complications induced by fructose consumption in hypertensive rats. - Danielle da Silva Dias; Nathalia Bernardes; Filipe Fernandes Stoyell-Conti; Camila Paixão Dos Santos; Amanda Aparecida de Araujo; Susana Llesuy; Maria Cláudia Irigoyen; Kátia De Angelis (PLoS ONE)
[This corrects the article DOI: 10.1371/journal.pone.0233785.].